A DIALOG ON ORGAN AND TISSUE DONATION: GAMIFICATION IN PERMANENT EDUCATION IN HEALTH - Lucas Vinícius de Lima; Gabriel Pavinati; Luciane de Assis Rocha Gonçalves; Carlos Alexandre Curylofo Corsi; Ellen Catarine Cabianchi; Rosane Almeida de Freitas; Vanessa Denardi Antoniassi Baldissera (Universidade Federal do Paraná, 2023)
Objective: to systematize the teaching-service partnership experience in the creation and application of a virtual game on organ and tissue donation as a proposal for permanent education in health. Method: systematization of an experience, conducted through documentary analysis, involving the process to create and apply an educational gamification practice by Nursing students, professors and professionals who developed the strategy and applied it at a university hospital in southern Brazil in September 2020. Results: given the health context imposed by COVID-19, the virtual game consisting of 20 questions about the organ and tissue donation process for transplants, as a strategy for ongoing health education, inspired engagement and motivation among the professionals, who showed limited knowledge about the theme and evaluated the strategy as positive. Conclusion: a potential path to be replicated in different contexts and scenarios was made evident, stimulating and encouraging the care and education processes.